Social context of the family structure and the quality of adolescents’ life: comparison of two-parent and single-parent families - Jaredic, Biljana N.; Radojevic, Tatjana S.; Radovic, Olivera B. (Sociološki pregled, 2026)
The research examinee the differences between adolescents from two-parent and single-parent families in social strategies, family interactions and temporal life satisfaction. The sample consisted 202 adolescents aged 14–19. Relevant questionnaires were applied. The results show that social strategies and family interactions predict a significant percentage of the temporal satisfaction variance. Adolescents from two-parent families show a greater sense of community and greater life satisfaction, while conflict and avoidance of social situations are more pronounced in single-parent families. Family earnings and the children’s age at the time of the parents’ separation are positively related to life satisfaction.